2018
DOI: 10.1007/s00204-018-2307-8
|View full text |Cite
|
Sign up to set email alerts
|

3,3ʹ-Dichlorobiphenyl (PCB 11) promotes dendritic arborization in primary rat cortical neurons via a CREB-dependent mechanism

Abstract: PCB 11 (3,3'-dichlorobiphenyl), a contemporary congener produced as a byproduct of current pigment production processes, has recently emerged as a prevalent worldwide pollutant. We recently demonstrated that exposure to PCB 11 increases dendritic arborization in vitro, but the mechanism(s) mediating this effect remain unknown. To address this data gap, primary cortical neuron-glia co-cultures derived from neonatal Sprague-Dawley rats were exposed for 48 h to either vehicle (0.1% DMSO) or PCB 11 at concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 71 publications
(100 reference statements)
1
39
0
Order By: Relevance
“…An early study reported that the hydroxylated metabolites of eight different LC-PCBs increase ROS formation and induce cell death in cultured cerebellar granule cells [245]. Later studies demonstrated that PCB 11 and its known human hydroxyl and sulfated metabolites increase dendritic arborization in primary rat hippocampal and cortical neurons [259]. These dendritic effects are observed in cultures exposed to PCB 11 at fM concentrations, which are within the range of PCB 11 concentrations detected in the serum of pregnant women [259].…”
Section: Emerging Evidence That Non-legacy Lc-pcbs Interfere With Typmentioning
confidence: 91%
See 4 more Smart Citations
“…An early study reported that the hydroxylated metabolites of eight different LC-PCBs increase ROS formation and induce cell death in cultured cerebellar granule cells [245]. Later studies demonstrated that PCB 11 and its known human hydroxyl and sulfated metabolites increase dendritic arborization in primary rat hippocampal and cortical neurons [259]. These dendritic effects are observed in cultures exposed to PCB 11 at fM concentrations, which are within the range of PCB 11 concentrations detected in the serum of pregnant women [259].…”
Section: Emerging Evidence That Non-legacy Lc-pcbs Interfere With Typmentioning
confidence: 91%
“…Later studies demonstrated that PCB 11 and its known human hydroxyl and sulfated metabolites increase dendritic arborization in primary rat hippocampal and cortical neurons [259]. These dendritic effects are observed in cultures exposed to PCB 11 at fM concentrations, which are within the range of PCB 11 concentrations detected in the serum of pregnant women [259]. In contrast to the HC-PCBs 95 and 136, PCB 11 and its metabolites not only increase dendritic arborization, but also enhance axonal growth [13].…”
Section: Emerging Evidence That Non-legacy Lc-pcbs Interfere With Typmentioning
confidence: 99%
See 3 more Smart Citations